Microwave Assisted Synthesis, Characterization and Biological Activities of Ferrocenyl Chalcones and Their QSAR Analysis - Yadav, Dinesh K.; Kaushik, Parshant; Pankaj,; Rana, Virendra S.; Kamil, Deeba; Khatri, Dilip; Shakil, Najam A. (Frontiers in Chemistry, 2019)
A new microwave method (MM) has been developed for the synthesis of a series of 16 substituted ferrocenyl chalcones using acetylferrocene (1) with different aldehydes (2a-2p) and comparing it with conventional method (CM). The synthesized compounds were characterized by various spectroscopic techniques viz IR, HR-MS, 1H NMR, and 13C NMR. The time required for completion of reaction in MM varied from 1 to 5 min as compared to CM which required 10–40 h. All the synthesized compounds were screened for antifungal activity against Sclerotium rolfsii and Alternaria solani. In vitro fungicidal activity revealed that compound 3o (ED50 = 23.24 mg L−1) was found to be most active against S. rolfsii. But in case of A. solani, compound 3c (ED50 = 29.9 mg L−1) showed highest activity. The nematicidal activity revealed that the compound 3b was more potent with LC50 values of 10.67, 7.30, and 4.55 ppm at 24, 48, and 72 h, respectively. 2D-Quantitative Structural Activity Relationship (2D-QSAR) analysis of these ferrocenyl chalcones was carried out by developing three different models namely Partial Least Squares (PLS, Model 1), Multiple Linear Regression (MLR, Model 2) and Principal Component Regression (PCR, Model 3). Statistical significance and predictive ability of these models were assessed by internal and external validation and also verified by leave one-out cross-validation. QSAR study revealed that MLR for S. rolfsii (r2 = 0.999, q2 = 0.996), PLS for A. solani (r2 = 0.934, q2 = 0.749) and PCR for M. incognita (r2 = 0.878, q2 = 0.772) were the best model. The physico-chemical parameters were calculated using VLife MDS 4.6 software. QSAR study could be employed for structure optimization to achieve better activity.